Use of modified atmosphere storage on postharvest quality of strawberries - Calegaro, Júlio Marques; Pezzi, Ernani; Bender, Renar João (Pesquisa Agropecuaria Brasileira, 2002)
Two experiments were conducted to test the use of three initial compositions of storage atmospheres (3 kPa O2 + 10 kPa CO2, 5 kPa O2 + 15 kPa CO2 or ambient air) and two storage periods (7 or 14 days) at 0oC on the quality of strawberries (Fragaria x ananassa Duch.) cv. Oso Grande. The fruits were originated from a grove of Farroupilha, RS, Brazil. In the first experiment, strawberries were stored in glass bottles with 1,700 mL of capacity. In the second experiment, polyethylene bags of 53 cm x 90 cm and 90 <span style="font-size: 12pt; font-family: Symbol; mso-ansi-language: EN-US; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">mm of thickness were used. The use of atmospheres with 3 kPa O2 + 10 kPa CO2 or 5 kPa O2 + 15 kPa CO2 resulted in a good storage potential of strawberries for up to 7 days. The modification of the atmosphere in polyethylene bags, using initial concentrations of ambient air also resulted in adequate fruit quality up to 7 days. The use of these atmospheres resulted in the maintenance of the pulp firmness, good fruit color and higher contents of total sugars and of ascorbic acid.